2022
DOI: 10.3390/molecules27154968
|View full text |Cite
|
Sign up to set email alerts
|

Selective Integrin α5β1 Targeting through Spatially Constrained Multivalent DNA-Based Nanoparticles

Abstract: Targeting cells specifically based on receptor expression levels remains an area of active research to date. Selective binding of receptors cannot be achieved by increasing the individual binding strength, as this does not account for differing distributions of receptor density across healthy and diseased cells. Engaging receptors above a threshold concentration would be desirable in devising selective diagnostics. Integrins are prime target candidates as they are readily available on the cell surface and have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The structure’s rigidity is related to sequence length (e.g., persistence length of the DNA double helix) as well as single- or double-stranded interactions . Finally, the complexity of DNA-based architectures ranges from low (a single helix) to very high, in the case of DNA-origami where hundreds of strands self-assemble into a macromolecular architecture of virtually any desired shape. ,,, Indeed, DNA-based nanomaterials have been used to explore the multivalent clustering of active cell surface receptors, and the importance of spatial organization was recently demonstrated in the case of apoptosis, , integrin targeting, and focal adhesion formation . The selective effect of patterns has been demonstrated in targeting of the dengue viral surface with aptamers organized in DNA star motifs .…”
Section: Introductionmentioning
confidence: 99%
“…The structure’s rigidity is related to sequence length (e.g., persistence length of the DNA double helix) as well as single- or double-stranded interactions . Finally, the complexity of DNA-based architectures ranges from low (a single helix) to very high, in the case of DNA-origami where hundreds of strands self-assemble into a macromolecular architecture of virtually any desired shape. ,,, Indeed, DNA-based nanomaterials have been used to explore the multivalent clustering of active cell surface receptors, and the importance of spatial organization was recently demonstrated in the case of apoptosis, , integrin targeting, and focal adhesion formation . The selective effect of patterns has been demonstrated in targeting of the dengue viral surface with aptamers organized in DNA star motifs .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, DNAscaffolded bivalent RGD ligands, displaying two RGD sequences in different spacings, were engineered to explore spatial distribution of integrin α5β1 on the cell surfaces of various cell lines. 123 A study carried out by Liu et al reported the generation and in vivo application of a DNA-structured cancer vaccine. The underlying nanostructures were composed of a DNA nanotube, which contained two types of toll-like receptor agonists (doublestranded RNA (dsRNA) and CpG DNA) along with a tumor antigen peptide (Fig.…”
Section: Templated Stimulation Of In Vitro and In Vivo Pathwaysmentioning
confidence: 99%
“…Additionally, DNA-scaffolded bivalent RGD ligands, displaying two RGD sequences in different spacings, were engineered to explore spatial distribution of integrin α5β1 on the cell surfaces of various cell lines. 123…”
Section: Templated Interactions With Biological Systemsmentioning
confidence: 99%
“…In contrast to other available nanoparticles, DNA origami offers perfect control over size, shape, and surface properties guaranteeing uniform particle design. In addition to their inherent biocompatibility, the modulatory properties of nucleic acid-based systems allow the positioning of individual ligand with nanometer precision. Benefiting from efforts on structural stabilization and surface characterization, the stability of DNA origami in biological environments as well as interactions with the biointerface are now well understood. Together, these features make DNA origami a platform for controlled ligand presentation for receptor binding susceptible to nanoscale ligand presentation.…”
mentioning
confidence: 99%